The portfolio book : a step-by-step guide for teachers - Shores, Elizabeth F.; Grace, Cathy (Beltsville, Md. : Gryphon House, 1998)
This book details a process for using student portfolios to support improved learning for children, teachers, and families, with the goal of encouraging reflection and goal-setting by individual learners and engaging parents in assessment and evaluation through frequent and varied communication. The book provides three major features: portfolio assessment theory, easy-to-use applications, and a complete set of reproducible forms. Chapter one of the book provides background information on assessment and evaluation, while chapter two summarizes how portfolios support child-centered learning and developmentally appropriate practice in early childhood education and care. Chapter three describes what teachers can do to get ready to implement the ten-step portfolio process. Chapter four outlines a typical portfolio and its contents. Chapter five guides the user through the ten-step portfolio process, showing how each step supports family participation and discussing how that involvement can make teachers and parents stronger allies. This chapter also shows how portfolio-based assessment is a process of innovation and adaptation. Three appendices provide a glossary of terms, sample forms of written materials, and a classroom equipment list. (SD).
Includes bibliographical references and index.
Keywords: Portfolios in education -- United States; Early childhood education -- United States